Advances in Mineral Processing and Hydrometallurgy - Anderson, Corby G.; Cui, Hao (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This is a Special Issue of Metals devoted to aspects of Advances in Mineral Processing and Hydrometallurgy. This includes a global call for article submissions that also included Characterization along with Recycling and Waste Minimization. As such, both primary and recycled aspects will be considered. Possible specific topics included Mineralogy, Geometallurgy, Thermodynamics, Kinetics, Comminution, Classification, Physical Separations, Liquid-Solid Separations, Leaching, Solvent Extraction, Ion Exchange, Activated Carbon, Precipitation, Reduction, Process Economics and Process Control. Suggested application areas were in Gold, Silver, PGM's, Aluminum, Copper, Zinc, Lead, Nickel, and Titanium. Critical Metals articles on topics such as Lithium, Antimony Tellurium, Gallium, Germanium, Cobalt, Graphite, Indium, and Rare Earth were also welcome. As such, this Special Issue of Metals was well supported by diverse submissions and the final publication of high-quality peer-reviewed articles.